How celebrity worship impact K-pop fans’ brand attitude, advertisement attitude, and repurchase intention towards local brands products - Swara Hati Nurani; Nurdin Sobari (President University, 2022)
The development of technology in this digital era makes it easier for marketing strategies to be carried out. One of which is by using celebrities who are in great demand by the target market even if they are cross-cultural, like the popularity of K-pop celebrities who are currently taking over the world. So many brands work with K-Pop celebrities on their marketing efforts, hoping to reach their famous loyal fans as a new market segment. This study investigates the relationship between K-pop fans’ celebrity worship on brand attitude, advertisement attitude, and repurchase intention. The test was conducted via an online survey with the snowball sampling method via social media and online fan communities. The test used the Celebrity Attitude Scale (CAS) on K-pop fans in Indonesia who had purchased K-pop merchandise from brands endorsed by K-pop celebrities and analyzed using PLS-SEM. The results show that although almost all dimension of celerity worship has a positive and significant influence on brand attitude, advertisement attitude, and repurchase intention, the entertainment-social dimension of celebrity worship was found to have no significant relationship with repurchase intention. However, from the overall results, we know that using K-pop celebrities is a great marketing strategy because their fans’ celebrity worship is found to be related to their intentions to repurchase any products from brands that endorse K-pop celebrities. The findings of this study will enrich marketers’ knowledge to formulate what marketing strategy to use for K-pop celebrity fans as a target market.